Strategi Pengembangan Produk Baitut Tamwil Muhammadiyah (BTM) dalam Meningkatkan Keunggulan Bersaing : (Pada KSPPS BTM Sumatera Barat Cabang Sungai Rumbai) - Sindy Amelia; Jon Kenedi (Universitas 45 Surabaya, 2024)
This research aims to formulate a product development strategy that will be carried out by KSPPS BTM West Sumatra Sungai Rumbai Branch in increasing its competitive advantage. The research method used is field research using qualitative descriptive methods. Research data collection techniques are documentation, interviews and observation. The data analysis method used is SWOT analysis which uses IFE, EFE analysis, SWOT matrix, and score weight table analysis to identify and analyze factors. From the research results, the Baitul Tamwil Muhammadiyah (BTM) product development strategy at KSPPS BTM West Sumatra Sungai Rumbai Branch has an IFE matrix analysis that produces an overall score of 3.5, which means taking advantage of the advantages of the BTM cooperative and maximizing internal factors, this has been achieved. EFE matrix analysis produces an overall score of 3.15 which shows that the BTM cooperative is very responsive to external factors by taking advantage of existing opportunities. The weighted score of the SO strategy is 3.9, the WO strategy is 3.2, the ST strategy is 3.45, and the WT strategy is 2.75. Based on the weighted assessment, the SO strategy score has the highest points compared to other strategies. The weighted evaluation is based on the contribution of the strengths or weaknesses to the achievement of the company's goals, vision and mission. The higher the weight, the greater the contribution and influence on achieving the company's goals, vision and mission, where the Strength Opportunities (SO) assessment can be used as a strategy to capture and utilize strengths in order to seize as many opportunities as possible from competitors.